Multimodality imaging evaluation of primary testicular extranodal natural killer/T-cell lymphoma: two case reports - Huang, Wenpeng; Liu, Xiaonan; Li, Liming; Zhang, Yongbai; Gao, Yuan; Gao, Jianbo; Kang, Lei (Frontiers in Medicine, 2023)
Background: Extranodal natural killer/T-cell lymphoma (ENKTCL) is a distinct pathological entity and accounts for approximately 10% of T-cell lymphomas. ENKTCL is typically aggressive and mainly affects the nasal cavity and nasopharyngeal region. However, some patients can present with distant nodal or extranodal involvement such as the Waldeyer ring, gastrointestinal tract, genitourinary organs, lung, thyroid, skin, and testes. Compared to ENKTCL of nasal type, primary testicular ENKTCL is very rare and has a lower age of onset and faster clinical progression, with tumor cell dissemination occurring early in the disease. Case Report: Case 1: A 23-year-old man presented with 1 month of right testicular pain and swelling. Enhancement CT revealed increased density in the right testis, uneven increased enhancement, discontinuity of the local envelope, and multiple trophoblastic vessels in the arterial phase. Testicular ENKTCL was diagnosed by postoperative pathology. The patient underwent a follow-up 18F-FDG PET/CT imaging 1 month later and found elevated metabolism in the bilateral nasal, left testicular, and right inguinal lymph nodes. Unfortunately, the patient received no further treatment and died 6 months later. Case 2: A 2-year-old male child presented with an enlarged right testicle, MRI showed a mass in the right epididymis and testicular area, which showed low signal on T1WI, a high signal on T2WI and DWI, and low signal on ADC. Meanwhile, CT showed soft tissue in the lower lobe of the left lung and multiple high-density nodules of varying sizes in both lungs. Based on the post-operative pathology, the lesion was diagnosed with primary testicular ENKTCL. The pulmonary lesion was diagnosed as hemophagocytic lymphohistiocytosis associated with EBV infection. The child was given SMILE chemotherapy, but pancreatitis was induced during chemotherapy, then he died 5 months later after chemotherapy. Conclusion: Primary testicular ENKTCL is very rare in clinics, which is mostly with a combined painful testicular mass as the first symptom and is easily misdiagnosed as an inflammatory lesion.18F-FDG PET/CT plays pivotal roles in the diagnosis, staging, evaluation of treatment outcomes and prognosis evaluation in patients with testicular ENKTCL, and it is helpful to assist clinical practice to better formulate individualized treatment plans.